Aktifitas Skills Lab di Masa Pandemi COVID-19 - Muhammad Anas; Muhamad Reza Utama (PROCEEDING UMSURABAYA, 2020)
AbstractThe current condition of the COVID-19 pandemic has changed the learning system, which wasoriginally fully face-to-face or blended, to be fully online. Skills lab, as one of the most routinemedical skills education methods in the undergraduate medical education phase, must alsoadapt its implementation by optimizing the full-online approach. Peyton's 4-stage of clinicalskill teaching is one of the approaches recommended by many medical education experts tofacilitate the online skills lab learning process during this pandemic.Keyword: Skills Lab, COVID-19, Pandemic, Online, distance learning, remote learning,Peyton's